2014
DOI: 10.1186/1756-0500-7-557
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of metallo-beta-lactamase producing clinical isolates of Escherichia coli and Klebsiella pneumoniae in central Nepal

Abstract: BackgroundThe increasing and rapid spread of metallo-beta-lactamase (MBL) producing Enterobacteriaceae, particularly Escherichia coli and Klebsiella pneumoniae represents an emerging public health threat. However, limited data is available on MBL production in clinical isolates of E. coli and K. pneumoniae from Nepal. We have therefore undertaken this study to ascertain the incidence of MBL production in clinical isolates of E. coli and K. pneumoniae at a tertiary care teaching hospital in central Nepal.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
34
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 25 publications
11
34
8
Order By: Relevance
“…Majority of MBL isolates were isolated from ICUs (82.1%). Our findings are in accordance with several studies, which found that the majority of clinical isolates were yielded from blood cultures and from patients in the ICU (Bora et al, 2014;Sultan et al, 2013;Shibl et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Majority of MBL isolates were isolated from ICUs (82.1%). Our findings are in accordance with several studies, which found that the majority of clinical isolates were yielded from blood cultures and from patients in the ICU (Bora et al, 2014;Sultan et al, 2013;Shibl et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies also found that the combined disc test was a highly sensitive (100%) method among the analyzed procedures (Picao et al, 2008;Galani et al, 2008b;Bora et al, 2014). This could be attributed to the subjective interpretation of DDST results.…”
Section: Discussionmentioning
confidence: 88%
“…Table 5 OB (200) 1 (20) 4 (80) OFX (10) 4 (80) 1 (20) AK (10) 5 (100) 0 (0) from both community and hospital samples [1,[3][4][5]. Our result on the prevalence of MBL-and AmpC-producing bacteria does not correspond to previous study in which E. coli and Klebsiella species that produced MBL and AmpC enzymes was reported at a higher rate [1,15,23,26,27]. The MBL-producing E. coli isolate and AmpC-producing Klebsiella species were multiply resistant to 7 antibiotics.…”
Section: Discussioncontrasting
confidence: 65%
“…CP-CRE prevalence rates are approximately 18% in two large hospitals in Nepal (99, 101). The most common carbapenemase in Enterobacteriaceae is NDM (101,102), with two new variants (NDM-8 and -12) described in Nepal recently (103,104). No mcr-positive Enterobacteriaceae have been found in Nepal to date.…”
Section: South Asiamentioning
confidence: 99%